2017
DOI: 10.1111/cea.12866
|View full text |Cite
|
Sign up to set email alerts
|

Role of ROCK2 in CD4+ cells in allergic airways responses in mice

Abstract: Background Rho kinases (ROCKs) contribute to allergic airways disease. ROCKs also play a role in lymphocyte proliferation and migration. Objective To determine the role of ROCK2 acting within CD4+ cells in allergic airways responses. Methods ROCK2 haploinsufficient (ROCK2+/-) and wildtype mice were sensitized with ovalbumin (OVA). ROCK2+/- mice then received either CD4+ cells from ROCK2 sufficient OVA TCR transgenic (OT-II) mice or saline i.v. 48 hours before challenge with aerosolized OVA. Wildtype mice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Moreover, ROCK2 ϩ/Ϫ mice showed reduced AHR via effects within airway smooth muscle cells in murine asthma model (28). In addition, airway smooth muscle cells and activation of RhoA and ROCKs enhance methacholine-induced contraction via retention of myosin light chain in a phosphorylated state, which favors contraction (28,31). We found a significant increase in RhoA and ROCK2 activity after HCl instillation, which was ameliorated through blockade of L-HA signaling, either through competitive inhibition by H-HA or by genetic deficiency of HA receptor CD44.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, ROCK2 ϩ/Ϫ mice showed reduced AHR via effects within airway smooth muscle cells in murine asthma model (28). In addition, airway smooth muscle cells and activation of RhoA and ROCKs enhance methacholine-induced contraction via retention of myosin light chain in a phosphorylated state, which favors contraction (28,31). We found a significant increase in RhoA and ROCK2 activity after HCl instillation, which was ameliorated through blockade of L-HA signaling, either through competitive inhibition by H-HA or by genetic deficiency of HA receptor CD44.…”
Section: Discussionmentioning
confidence: 98%
“…It is thus likely that sustained production of L-HA is achieved through neutrophil influx, which sustains the inflammatory response, barrier disruption and, AHR development. Recent studies showed that L-HA increases vascular permeability by activating small GTPases (such as RhoA), which in turn induce actin cytoskeletal reorganization; inhibit endothelial cell-cell contacts (36),; activate ROCK, their downstream kinases (28), and Ca 2ϩ channels (such as TRPC); and increase Ca 2ϩ influx from the extracellular milieu to the cytoplasm (46). Moreover, ROCK2 ϩ/Ϫ mice showed reduced AHR via effects within airway smooth muscle cells in murine asthma model (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects of Y‐27632 may well be due to the suppression of enhanced calcium sensitization of airway smooth muscle contraction induced by allergen‐sensitization , and effects of ROCK inhibition on chemotaxis of inflammatory cells. Studies using ROCK hetero‐deficient mice indicate that both ROCK1 and ROCK2 in lymphocytes and nonlymphocyte cells are involved in these processes .…”
Section: Rho Signaling Research In Current Statusmentioning
confidence: 99%